The Role of Management Accounting in Promoting Organizational Performance: A Literature Review - Pedroso, Elsa (2020)
The information has become one of the essential resources for companies that want to be competitive in the global market. To use this information, they need management practices that promote the collection and processing of that information internally, but also from the external competitive environment. In this context, the objective of this study is to analyze the role of management accounting in companies, contributing to the increase of its effective use and consequently to improve organizational performance. It is also intended to identify opportunities for future research on this subject. To achieve this objective, a literature review of the empirical studies related to management accounting published in the last 20 years was carried out. The main results show too much concern from researchers with the internal variables that can influence the effective use of management accounting. However, they may be neglecting the communication channels with the market and, thus, losing competitiveness.